The evolution of the form of lyric hero in travel essays at Belarusian TV in 1960–90s - Morozowa, Elena I. (Journal of the Belarusian State University. Journalism, 2019)
The aim of the study is to examine the characteristics of travel essay at Soviet television. It is proved that there are lot of chronical documentary films that had the features of the genre. Travel essays were similar to other genres (problem reportage, for example). It’s a distinguishing feature of travel essays. The evolution of the genre at Soviet TV linked with the evolution of subjectivism and the role of lyric hero: firstly a neutral person, secondly a person of traditional culture and thirdly an active open-minded person. A. Chylanov revived the continuity of the traditions of the genre with its romantic hero.